Bureau of Transport and Regional Services - Department of Transport & Regional Services (Department of Transport & Regional Services, 2005)
In this booklet, the main spatial concept used to summarise information about Australia's regions is the ABS Remoteness Structure. This classification groups Census Collection Districts into five broad classes of remoteness, which share common characteristics in terms of physical distance from services and opportunities for social interaction. These classes are: Major Cities of Australia; Inner Regional Australia; Outer Regional Australia; Remote Australia; and Very Remote Australia. Remoteness classes cut across State and local government boundaries, enabling understanding of the patterns of socio-economic experience across Australia's regions.
About Australia’s regions 2005
Keywords: Housing, communities and neighbourhoods; Housing, communities and neighbourhoods